IMPROVING STUDENTS’ ACHIEVEMENT IN LEARNING CIRCLE LESSON OF MATHEMATICS BY GROUP WORK METHOD AT JUNIOR HIGH SCHOOL (SMPN) 4 LOA JANAN - Sukardi Sukardi (Acitya: Journal of Teaching and Education, 2019)
The aim of the study was to investigate how the teaching method of group work could improve students’ achievement in learning one of the mathematics lessons, the circle. A study about the use of group work method is expected to solve the problem faced by the teacher by a systematic thinking framework. Therefore the researcher collaborated with his peer to conduct the research. This classroom action research study was conducted at Junior High School (SMPN) 4 Loa Janan. The participants of the research were all the students from the eighth grade. The procedures of the study were conducting pre-test, lesson planning for action research, implementing the lesson with proposed method, observing the lesson, reflection, and evaluation. The study was conducted in three cycles. The results showed that there was an improvement in students’ mathematics academic achievement. This was proven by the students’ test results from one cycle to another that the student scored significantly above 80% above minimum criteria